Overview of anomaly detection techniques for industrial Internet of things - Haili SUN; Xiang LONG; Lansheng HAN; Yan HUANG; Qingbo LI (Tongxin xuebao)
In view of the differences of existing anomaly detection methods and the applicability when applied to security protection of the industrial Internet of things (IIoT), based on technical principles, the network anomaly detection papers published from 2000 to 2021 were investigated and the security threats faced by IIoT were summarized.Then, network anomaly detection methods were classified into 9 classes and the characteristics of each class was studied.Through longitudinal comparison, the merits and shortcomings of different methods and their applicability to IIoT scenarios were sorted out.In addition, statistical analysis and comparison of common data sets were made, and the development trend in the future was forecasted from 4 directions.The analysis results can guide the selection of adaptive methods according to application scenarios, identify key problems to be solved, and point out the direction for subsequent research.